2023
DOI: 10.1029/2022gl101170
|View full text |Cite
|
Sign up to set email alerts
|

Muon Imaging of Volcanic Conduit Explains Link Between Eruption Frequency and Ground Deformation

Abstract: Forecasting the location, onset, cessation, and style of impending volcanic eruptions facilitates effective mitigation of the impact of associated hazards (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…5 W. These instruments can Black rectangles show the tracking layers and hatched rectangles show the lead shielding plates applied for absorbing and deflecting the low-energy particles which do not penetrate the structure to be imaged but observed from its directions. be supplied by two 100 Ah batteries for more than two weeks on remote sites (e.g., see [24,25,26]). These instruments have already been applied successfully for muography of Earth's subsurface [24,25] and human-made infrastructures [26,27].…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 W. These instruments can Black rectangles show the tracking layers and hatched rectangles show the lead shielding plates applied for absorbing and deflecting the low-energy particles which do not penetrate the structure to be imaged but observed from its directions. be supplied by two 100 Ah batteries for more than two weeks on remote sites (e.g., see [24,25,26]). These instruments have already been applied successfully for muography of Earth's subsurface [24,25] and human-made infrastructures [26,27].…”
Section: Instrumentationmentioning
confidence: 99%
“…be supplied by two 100 Ah batteries for more than two weeks on remote sites (e.g., see [24,25,26]). These instruments have already been applied successfully for muography of Earth's subsurface [24,25] and human-made infrastructures [26,27].…”
Section: Instrumentationmentioning
confidence: 99%
“…The first important muography experiment in this area focused on the summit of Mount Asama, Japan 80 , in 2007. Since then, density distributions have been muographically acquired for several volcanoes including Usu, Japan 81 , Showa-Shinzan lava dome, Japan 43 , Asama, Japan 80,82,83 , Izu peninsula, Japan 84 , Omuroyama, Japan 85 , Unzen, Japan 86 , Shinmoedake, Japan 87 , Sakurajima, Japan 88,89 , Satsuma-Iwojima, Japan 90,91 , La Soufrière, France 92 ), Puy de Dome, France 93 , Etna, Italy 94 , Vesuvius, Italy 30 , and Stromboli, Italy 95 . The volcanological targets that can be imaged include magma movements 91 , plug formation 89 , crater floor collapse 94 , hydrothermal deformation 96 , and tephra deposition and erosion 97,98 .…”
Section: Muographic Imagerymentioning
confidence: 99%
“…Recently, muography data have been combined with gravimetry 99,100,101 , seismotomography 102 ) and satellite-based interferometric synthetic aperture radar (InSAR) 89 . Knowing the magma rise evolution process in the conduit of a volcano as early as possible buys critically important time for initiating alarm and evacuation protocols.…”
Section: Muographic Imagerymentioning
confidence: 99%
“…Notable studies by Nishiyama et al 43 and Lesparre et al 44 have discussed the correlation between gravity inversion results and muographic surveys for imaging the internal density of volcanoes. Oláh et al 45 demonstrated the utility of muography as a support tool for ground surface deformation monitoring techniques, enhancing the modeling of eruptive processes for forecasting purposes. In addition, significant advancements have been made in the field of mining survey measurements over the past decade 46 .…”
mentioning
confidence: 99%